Characteristics of methane desorption and diffusion in coal within a negative pressure environment. (1st April 2018) - Du, Yunfei; Chen, Xiangjun; Li, Liyang; Wang, Peng
Highlights: Methane desorption and diffusion properties were studied in coal in a negative pressure environment. Time-dependent desorption, at different negative pressure gradients, takes the form of a Langmuir adsorption isotherm. Interfacial mass transfer resistance decreases, and the diffusion coefficient and Fourier's criterion of mass transmission increase. Increasing negative pressure changes the coal diffusion kinetics and enhances diffusion capacity. Abstract: To study the characteristics of gas diffusion and changes in the dynamic parameters of coal under a negative pressure environment, experiments were performed to constrain the desorption process under different negative pressures in coal samples at (0.5, 1.5 and 2.5) MPa adsorption equilibrium pressures. The experimental results demonstrate that the relation curves between time and the desorption quantities of coal samples with different negative pressures have shapes similar to that of Langmuir's adsorption isotherm. In addition, all coal samples with different negative pressures have a maximum regarding methane desorption. As the negative pressure increases from 10 kPa to 40 kPa, the limitation gas desorption amount increases from 8.73 to 10.93 mL/g, from 14.91 to 17.75 mL/g, and from 18.30 to 23.27 mL/g, respectively, under 0.5 MPa, 1.5 Mpa and 2.5 Mpa adsorption equilibrium pressure. Moreover, under the same adsorption pressure, the larger the negative pressure becomes, the greater the gas desorption velocity of the first minute ( V1 ) is. The change of gas desorption velocity with negative pressure during the first minute is an exponential function. The performance under different adsorption equilibrium pressures demonstrates the same regularity. With the increase of negative pressure, interfacial mass transfer resistance also decreases, and the diffusion coefficient and Fourier's criterion of mass transmission increase. This indicates that the negative pressure environment changes the desorption kinetic-parameters of the coal mass and increases the amounts of methane desorption and desorption velocity, which are advantageous for desorption and diffusion of coal methane.